Advances in membrane technologies for water treatment : materials, processes and applications - Basile, Angelo (Angelo Bruno); Cassano, Alfredo; Rastogi, Navin K. (Cambridge, UK : Woodhead Publishing, 2015)
Annotation Water supplies are under mounting pressure due to population growth, urbanisation, reliance on intensive agriculture and a changing climate. Against this background, there is intensive research into water treatment technologies to reduce water shortages. This book provides a detailed overview of advanced water treatment methods involving membranes, which are increasingly seen as effective replacements for a range of conventional water treatment methods. Opening chapters review recent developments in membrane materials and focus on advances in membrane operations. Contributions in part two then focus on methods to improve membrane performance, for example reducing fouling. The final part of the book addresses applications of membranes for different types of water treatment.
Includes index.
Includes bibliographical references at the end of each chapters and index.
Online resource; title from PDF title page (ScienceDirect, viewed March 12, 2015).
Elsevier
Keywords: Water -- Purification -- Membrane filtration; Membranes (Technology); TECHNOLOGY & ENGINEERING / Environmental / General; Membranes (Technology); Water -- Purification -- Membrane filtration; Electronic books; Electronic books